Exploring the Development of Teacher Resilience through Mobilizing Teacher Education: A Case Study of Early Childhood Educators in Purwakarta - Dede Hikmah; Sri Wulan; Elindra Yetti (AL-ISHLAH: Jurnal Pendidikan, 2025)
Resilience is a critical competency for Early Childhood Education (ECE) teachers, particularly in adapting to evolving educational demands. This study examines how participation in the Mobilizing Teacher Education program fosters resilience among ECE teachers. A qualitative case study approach was employed, involving four mobilizing teachers from Batch 7 in Purwakarta district. Participants were selected based on their active involvement in the program. Data were collected through observations, interviews, and document analysis. Triangulation and data validation tests were conducted to ensure reliability. Findings indicate that the program positively influences teacher resilience, enhancing their ability to adapt to 21st-century educational challenges, strengthening leadership skills, and improving professional competencies. However, participants faced several challenges, including limited internet access, insufficient school support, conflicts between program requirements and personal responsibilities, financial constraints, and teamwork difficulties. Time management issues often led to stress and health concerns. The study highlights the need to sustain and improve the Mobilizing Teacher Education initiative by addressing structural challenges. Enhancing institutional support, optimizing task allocation, and providing financial or logistical assistance can help mitigate obstacles. While the program fosters resilience and professional growth, its sustainability requires adjustments to reduce teacher burden. Restructuring workloads and improving resource allocation are essential to ensure a more effective and enduring professional development experience.